PROFIL PEDAGANG KAKI LIMA STUDI PEDAGANG MIRAS - Putra, Ricky Erianza; ", Syafrizal (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2014)
One of the informal sector that many people acted by the weak economy is as street vendors ( PKL ) . The existence of street vendors has been growing for a long time and the numbers continue to grow as the demands of the growing economy and to fewer opportunities in the formal sector . One street trading business in the city of Pekanbaru precisely on Jalan Ir . Juanda is Street Vendor liquor . Their existence has been around a long time with the source material acquisition merchandise liquor from the nearest port . The street vendors came from all regions of about Pekanbaru well as by local residents and from outside the city of Pekanbaru . The existence of Street Vendors of this liquor is one of the distribution points liquor illegally because they also obtain merchandise from unauthorized or illegal sources . Researchers interested in this case to review the profile hawkers on street vending liquor Ir . Juanda . The purpose of this study is to determine the type of social relationships between vendors and to find out how to obtain and sell alcohol .Keeword: profile, street,vendors